Islamic Finance and Economic Growth: A Bibliometric Analysis of Scholarly Contributions - Judijanto, Loso (Westscience Press, 2025)
This study presents a comprehensive bibliometric analysis of scholarly contributions at the intersection of Islamic finance and economic growth. Using data extracted from the Scopus database and analyzed through VOSviewer software, the research maps the intellectual structure, thematic evolution, and collaborative networks within this growing academic domain. The findings reveal a significant increase in publication volume since 2015, peaking in 2024, with Malaysia leading in research output and international collaboration. The co-occurrence analysis identifies key thematic clusters centered around Islamic banking, financial development, social finance, and emerging areas such as Islamic fintech and sustainability. Influential scholars such as M.K. Hassan and A. Mirakhor, along with foundational economic theories, shape the field’s discourse. The country and institutional collaboration networks highlight a regional concentration in Southeast Asia and the Middle East, while also reflecting the increasing involvement of global North institutions. Despite the field's growth, research gaps remain in geographical inclusivity, empirical validation, and innovation-focused studies. This study provides a structured overview of existing literature and offers directions for future research at the nexus of Islamic finance and sustainable economic development.